1982
DOI: 10.1136/bmj.285.6349.1168
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of urine specific gravity and osmolality using a simple reagent strip.

Abstract: giving potassium supplements to elderly patients where their need is not urgent. Since the absorption of fluid from the infusion site is slow, we do not recommend this method for giving potassium when large amounts are needed urgently. There seems to be no danger of hyperkalemia with the method used here.Although hypodermoclysis is suitable for use in nursing homes, we feel that subcutaneous potassium infusions should be given only in hospitals until more experience is gained.We would like to thank Cilla Gerbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…It is thought that glucose does not affect the relationship between SG and osmolality (13,14) and it is controversial whether protein does so (5). In our study, we found that proteins, glucose, ketones, bilirubin, urobilinogen all affect the relationship between SG and osmolality.…”
Section: Discussioncontrasting
confidence: 42%
“…It is thought that glucose does not affect the relationship between SG and osmolality (13,14) and it is controversial whether protein does so (5). In our study, we found that proteins, glucose, ketones, bilirubin, urobilinogen all affect the relationship between SG and osmolality.…”
Section: Discussioncontrasting
confidence: 42%
“…SG is readily measured by reagent strip for field studies without needing a laboratory. Previous studies demonstrate good agreement between SG measurements by reagent strip versus refractometer 29,30 or osmolality. 3032 SG measurement by reagent strip is widely used in clinical applications.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies demonstrate good agreement between SG measurements by reagent strip versus refractometer 29,30 or osmolality. 3032 SG measurement by reagent strip is widely used in clinical applications. 32,33 Although refractometer urine SG may be influenced by disease states leading to high serum protein or glycosuria, 7,34 reagent strip SG is not affected by glucose, only minimally by urea and albumin, but may be affected by the rare instances of alkaline urine.…”
Section: Discussionmentioning
confidence: 84%
“…Recently we published our initial results on the empirical correlation of the test strip indication (SG) and urinary osmolality (1). In the meantime, contradictory results (2)(3)(4)(5)(6)(7)(8), based on a rather small number of urine samples, have been published. We now report a cornprehensive evaluation, which defines more precisely the feasibility and limitations of the SG field.…”
Section: Introductionmentioning
confidence: 96%